2002
DOI: 10.1038/sj.mn.7800125
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Urate on Nitric Oxide Microcirculatory Response in the Rat Tail to Body Heating

Abstract: Urate at physiological concentration helps to maintain vascular conductance of cutaneous capillaries in the rat tail during body heating. The effect of urate on vascular conductance may be mediated by NO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…In our study, the average temperature of the T1D patients during exercise was 37.8 ± 0.8 ° C, which may have been an important stimulus for the changes in capillary perfusion. In this sense, because it has been shown that physiological levels of urate are needed to promote increases in capillary perfusion in thermal stress situations [ 67 ], it is reasonable to speculate that the decrease in uric acid levels represents improvements in perfusion associated with the adaptive effects of low intensity training and resulting in capillary angiogenic processes.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the average temperature of the T1D patients during exercise was 37.8 ± 0.8 ° C, which may have been an important stimulus for the changes in capillary perfusion. In this sense, because it has been shown that physiological levels of urate are needed to promote increases in capillary perfusion in thermal stress situations [ 67 ], it is reasonable to speculate that the decrease in uric acid levels represents improvements in perfusion associated with the adaptive effects of low intensity training and resulting in capillary angiogenic processes.…”
Section: Discussionmentioning
confidence: 99%